Introspecção do desenvolvimento pessoal no contexto de uma trajetória acadêmica na medicina - Costa, Luciano Quint Alves da (Universidade Federal de São Carlos, 2024)
The following work, in accordance with requirements, has the intrinsic objective of instigating a reflection on the trajectory taken in professional training in a unique way for each graduating student. This is possible because, despite common elements among the students, each path taken was unique. Thus, from the perspective of a reflection centered on each moment and stage of the journey in medicine at UFSCar, the aspects that made up the moments experienced by the author throughout his academic journey will be visited in an introspective way, not just from the point of view of describing events, but from a personal level. With temporal divisions between the periods grouped together given the similar characteristics they share, the text will go through 4 large sections until concluding with final considerations of the moment before the end of the degree.
Introspection of personal development in the context of an academic career in medicine
Keywords: Introspecção; Medicina; UFSCar; Educação médica; Introspection; Medicine; CIENCIAS DA SAUDE::MEDICINA